A Comparative Evaluation of Multi-Criteria Decision Analysis Techniques for Selecting the Appropriate Vector Management Strategy in the Northern Zone of Plateau State, Nigeria (American Journal of Multidisciplinary Research and Innovation, 2024)
Accurate assessment of the complexity of malaria transmission dynamics requires the selection of appropriate Multi-Criteria Decision Analysis (MCDA) techniques that enable thorough analysis of risk factor parameters and structuring of decision problems into well-defined outcomes. A comparative study and analysis of multi-criteria decision-making methods such as TOPSIS, PROMETHEE II, MAUT and COPRAS was carried out using the reference rankings of MULTIMOORA and MOOSRA to evaluate the consistency of the results of these techniques and to rank the risk factors according to the vulnerability of mosquito breeding habitats and the risk of malaria transmission in the study area. The results indicate that TOPSIS ranked the alternative similarly to the reference ranking, while PROMETHEE II, MAUT, and COPRAS were ranked equally according to the weighted Spearman correlation coefficient and the weighted sum rank similarity coefficient analysis. The degree of consistency with which the risk factors in the study area were analyzed through this comparative study shows that the TOPSIS technique is suitable for its application in malaria epidemiology to determine the appropriate intervention measure for vector management in the northern zone of up to certain Plateau State.